Community pharmacists' decision-making patterns in clinical prescription checking: A simulation-based study - Ali Elgebli; Jason Hall; Denham L. Phipps (Exploratory Research in Clinical and Social Pharmacy)
Background: Community pharmacists (CPs) make a significant number of decisions on the clinical appropriateness of prescriptions daily to ensure safe and effective use of medications, in a process known as “clinical checking”. The process is complex and is affected by multiple factors in practice. This study aimed to investigate the cognitive processes involved in clinical prescription checking by CPs. Method: This qualitative study employed a purposive sampling technique to recruit a diverse sample from the population of CPs in England. Engaging in Zoom interviews, participants clinically checked three simulated prescriptions, providing concurrent verbal accounts of their thoughts. The participants' commentaries during the task were audio-recorded, transcribed verbatim, and underwent deductive thematic analysis based on Klein's recognition-primed decision-making (RPD) model. Results: Twelve CPs from diverse backgrounds and varied working conditions were recruited and completed the online checking task. Making decisions on the clinical appropriateness of prescriptions appeared to be a multi-staged procedure whereby several levels of concerns exist, and pharmacists vary in their ability to recognise and resolve those concerns. CPs behaved in a manner similar to that described by the RPD model; they mostly engaged in pattern-recognition during clinical checking, but adopted a more analytical approach when they recognised an atypical situation. Participants showed more consistency when processing cues and expectancies; however, their subsequent actions exhibited substantial variability, coupled with a degree of hesitancy. Conclusion: Clinical checking of prescriptions is a multifaceted process in which pharmacists employ a blend of pattern recognition and analytical thinking when making decisions. The process differs notably among pharmacists, underscoring the need to understand the factors driving these variations and any hesitancy in decision- making, as well as their potential impact on patient safety.